Households' Response Strategies to Rubber Land Deal Shocks in the Ahanta West District, Ghana (Global Journal of Human-Social Science, 2021)
Abstract not found
Keywords: land deal shocks; multivariate probit; response strategies; para rubber; ahanta west; ghana